Lomba Mewarnai Sebagai Program Kerja Edukatif KKN UNP 2026: Upaya Stimulasi Kreativitas Dan Motorik Halus Anak Usia Dini Di Nagari Sungai Rumbai Timur, Kabupaten Dharmasraya - Junil Adri; Dini Safira; Dela Puspita Sari; Farah Putri Afifi; Friska Alviona; Afif Muhammad Rijal (CV. ITTC INDONESIA, 2026)
The Community Service Program (KKN) of Universitas Negeri Padang (UNP) for the January-June 2026 period in Nagari Sungai Rumbai Timur, Dharmasraya Regency, West Sumatra Province, implemented an educational work program in the form of a Kindergarten-Level Coloring Competition. This program was designed in response to the importance of stimulating creativity and fine motor development in early childhood in rural areas that have not yet received optimal attention. This article uses a qualitative descriptive approach to analyze the implementation process, impact, and program relevance to early childhood potential development. The event held on January 28, 2026 was attended by 25 participants representing 5 kindergartens throughout Nagari Sungai Rumbai Timur. Results show that the coloring competition successfully stimulated children's visual expression, trained fine motor skills, improved concentration, and built participants' self-confidence. The activity received positive responses from all stakeholders and proves that synergy between KKN students, village government, and the community can create real impact on the quality of early childhood education in rural areas.